FORMULASI DAN UJI SIFAT FISIK GEL EKSTRAK ETANOL DAUN MURBEI (MORUS ALBA L.): FORMULASI DAN UJI SIFAT FISIK GEL EKSTRAK ETANOL DAUN MURBEI (MORUS ALBA L.) - Ambarsari, Niati; Tulak Rerung , Lola' (Journal of Pharmacy Tiara Bunda, 2025)
The use of plants as medicines in Indonesia has been going on for a long time. One example is mulberry leaves (Morus alba L.) which are traditionally used to treat burns. Mulberry leaf extract (Morus alba L.) contains secondary metabolites such as alkaloids, flavonoids, saponins, tannins and terpenoids. The presence of these contents in mulberry leaves has the potential as anti-inflammatory, antibacterial and antioxidant. This research aims to prepare and test the physical properties of mulberry leaf extract gel (Morus alba L). The extraction method used is maceration. The gel formula is made with three extract concentrations, namely F I (1.5%), F II (2%) and F III (2.5%). The physical properties of the gel include organoleptic tests, pH, homogeneity, adhesion and spreadability. The results of all physical properties tests on formulas I, II and II met the requirements for gel preparations, but the spreadability test for formula I did not meet the requirements for gel preparations. From the results of the physical properties test of the ethanol extract gel of mulberry leaves (Morus alba L.) it can be concluded that formula III is the best and optimal formula.